Effect of Shading on the Performance of Vitis vinif era L. cv. Cabernet Sauvignon - Archer, E.; Strauss, H.C. (South African Journal of Enology and Viticulture, 2017)
The effect of shading on the performance of Cabernet Sauvignon was studied. Significant different levels of canopy density were created using the growth of neighbouring vines, thus ensuring no artificial change in natural light composition. Light penetration in these canopies differed significantly between treatments. Berry mass, bunch mass and yield as well as skin colour were decreased with increasing levels of shading, while pH, K-concentration and TT A were increased. Tartaric acid decreased while malic acid increased with an increase in shading. Wine quality was negatively affected.